2008
DOI: 10.3856/vol36-issue2-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

Estuarine and marine brachyuran crabs (Crustacea: Decapoda) from Bahia, Brazil: checklist and zoogeographical considerations

Abstract: ABSTRACT. The coast of the state of Bahia in eastern Brazil comprises more than 12% of the entire Brazilian coast. However, the crustacean fauna of this area still remains poorly known, especially the shallow-water fauna. We provide here a list of 162 brachyuran crustaceans known for the Bahia coast, based on published records as well as material deposited in the Carcinological Collection of the Universidade Estadual de Santa Cruz, Ilhéus, Bahia. The list includes estuarine and marine species (from coastal bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 42 publications
1
15
0
5
Order By: Relevance
“…Several studies have demonstrated that mollusks and crustaceans are the richest and most abundant taxa in marine benthic communities (Archambault & Bourget, 1996;De Almeida & Coelho, 2008); this has also been the case for Gorgona island and other places along the Pacific coast of Colombia, such as Bahía Málaga, Golfo de Cupica and Cabo Marzo (invemar et al, 2006;.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have demonstrated that mollusks and crustaceans are the richest and most abundant taxa in marine benthic communities (Archambault & Bourget, 1996;De Almeida & Coelho, 2008); this has also been the case for Gorgona island and other places along the Pacific coast of Colombia, such as Bahía Málaga, Golfo de Cupica and Cabo Marzo (invemar et al, 2006;.…”
Section: Discussionmentioning
confidence: 89%
“…This is a major barrier to the movement of marine species, forming a natural faunal boundary for many organisms (de Almeida and Coelho, 2008), and octopuses, as with most other cephalopods, cannot tolerate large seawater salinity fluctuations (Potts and Todd, 1965;Wells, 1978). However, any effects of the Amazon on the distribution of M. januarii are unclear, since initiation of the Amazon system (around 11 Mya; Figueiredo et al, 2009) may have occurred after M. januarii was already established in the Atlantic.…”
Section: Muusoctopus Januarii As An Amphi-atlantic Speciesmentioning
confidence: 99%
“…Mithrax tortugae Rathbun, 1920 -Geographic distribution: Western Atlantic -Florida, Antilles, Colombia, Venezuela and Brazil (Pará, Pernambuco, Alagoas and from Bahia to São Paulo and Santa Catarina) (Coelho et al, 1990;Melo, 1998;Rieger and Giraldi, 2001;Coelho et al, 2002;Almeida and Coelho, 2008).…”
Section: Resultsmentioning
confidence: 99%